THE ROLE OF TOURISM PLANNING IN MANAGING CROWDS OF MILLIONS AND SPECIAL TOURISM EVENTS A STUDY OF A SAMPLE OF PARTICIPANTS IN THE TUWAIRAJ RUN - Taha Mahdi Mahmood (Journal Park Publishing, 2023)
Tourism planning is considered one of the most critical contemporary sciences and a term with precise alphabets, as its development and importance are linked to the development of tourism as a cultural phenomenon with many economic and social dimensions that are affected by it. Tourism has become a human activity of great importance that it has not enjoyed in any previous era. These intense tourism activities resulted in economic, social, cultural, environmental, and urban results and impacts that had an apparent effect on the development of the lives of societies and peoples in our current era, which necessitated directing attention to the necessity of organizing, controlling and evaluating these activities to reach the desired and desired goals quickly and accurately without leaving any trace. One of its details resulted in the adoption of the tourism planning method as a specialized science that deals with studying, analyzing, and interpreting all tourism activities. It works to develop and develop them according to integration with the rest of the scientific and practical sciences.
Keywords: Planning, tourism planning, management, crowds, tourist events, Tuwairaj run.